Improving the Nutritive Value of Cocoa-Pod by Chemical Treatment. - Osafo, Emmanuel Lartey Kwame (Obafemi Awolowo University, 2014)
Two 'In Situ' studies were conducted to evaluate the effectiveness of cocoa-pod ash solutions (PAS) as an alkali for treating cocoa-pods. Feed intake and overall nutrient digestibility of PAS - treated cocoa-pod based diet by cheep and goats were evaluated in two separate trials. In a screening trial, 5g oven dried and untreated cocoa-pod (Upod) or cocoa-pod treated (1:1 volume/weight) with either 4 levels of NaOH, 2, 4, 6 and 8% or corresponding strengths of PAS, P2, P4, P6 and P8 were weighed into nylon bags (2* pore diameter) and incubated for 24 hours in the rumen of two cannulated adult dwarf sheep fed a 50% cocoa-pod diet. Results showed NDF, ADF and Lignin were reduced (P<.05) by increasing PAS or NaOH treatment. Both NaOH and PAS improved (P<.05) degradability of dry matter, NDF and ADF.